2017
DOI: 10.3791/55866
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Transcranial Alternating Current Stimulation and Functional Magnetic Resonance Imaging

Abstract: Transcranial alternating current stimulation (tACS) is a promising tool for noninvasive investigation of brain oscillations. TACS employs frequency-specific stimulation of the human brain through current applied to the scalp with surface electrodes. Most current knowledge of the technique is based on behavioral studies; thus, combining the method with brain imaging holds potential to better understand the mechanisms of tACS. Because of electrical and susceptibility artifacts, combining tACS with brain imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…A main hardware precaution to be aware of when bringing any electronic equipment into the MRI scanner is not allowing the wires to become RF transmitters and introduce noise into the MRI data. To prevent this, currently two similar hardware configurations for MRI‐compatible tDCS are used (Meinzer et al, ; Williams et al, ). The procedures are described below: Connect the leads from the tDCS power supply to an RF filter box (MRI control room), from the RF filter box to a nonmagnetic, shielded local network cable that enters the MRI scanner room via the RF waveguide tube, carefully oriented to reduce resonant capacitive coupling, and then finally sent through another RF filter box (MRI‐compatible, inside scanner room) before connecting to the tDCS electrodes (Figure a). Connect the leads from the tDCS power supply (MRI control room) to an RF filter attached to the penetration panel, and then connect the other end of the penetration panel (MRI scanner room) to the electrode leads (Figure b). …”
Section: Practical Considerations When Combining Tdcs With Functionalmentioning
confidence: 99%
See 1 more Smart Citation
“…A main hardware precaution to be aware of when bringing any electronic equipment into the MRI scanner is not allowing the wires to become RF transmitters and introduce noise into the MRI data. To prevent this, currently two similar hardware configurations for MRI‐compatible tDCS are used (Meinzer et al, ; Williams et al, ). The procedures are described below: Connect the leads from the tDCS power supply to an RF filter box (MRI control room), from the RF filter box to a nonmagnetic, shielded local network cable that enters the MRI scanner room via the RF waveguide tube, carefully oriented to reduce resonant capacitive coupling, and then finally sent through another RF filter box (MRI‐compatible, inside scanner room) before connecting to the tDCS electrodes (Figure a). Connect the leads from the tDCS power supply (MRI control room) to an RF filter attached to the penetration panel, and then connect the other end of the penetration panel (MRI scanner room) to the electrode leads (Figure b). …”
Section: Practical Considerations When Combining Tdcs With Functionalmentioning
confidence: 99%
“…A main hardware precaution to be aware of when bringing any electronic equipment into the MRI scanner is not allowing the wires to become RF transmitters and introduce noise into the MRI data. To prevent this, currently two similar hardware configurations for MRIcompatible tDCS are used (Meinzer et al, 2014;Williams et al, 2017).…”
Section: Mri-compatible Stimulator Setupmentioning
confidence: 99%
“…Several EEG/fMRI studies revealed how the manipulated oscillatory activity of tACS is represented in the brain’s metabolism while demonstrating that increased alpha and beta amplitudes correlate with deactivation in occipital areas measured by reduced blood oxygenation level dependent (BOLD) contrasts ( Cabral-Calderin et al, 2016 ; Williams et al, 2017 ). Moreover, Vosskuhl et al (2016) confirmed that entrainment of EEG alpha oscillations by tACS at the IAF reduces the BOLD response to visual stimuli ( Vosskuhl et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…tDCS effects with high spatial resolution across the entire brain [10]. Combining tACS with simultaneous fMRI has shown that the stimulation effects are state-, current-, and frequency-dependent, and that modulation of brain activity is not limited to the area directly below the electrodes [11].…”
Section: Introductionmentioning
confidence: 99%